Identifying the Private Prince Sultan University’s evaluation degree in light of the balanced scorecard in view of its employees - Alaskar, Sarah Fahad (Journal of Educational and Psychological Sciences, 2022)
The study aims to identify the Private Prince Sultan University’s evaluation degree in light of the balanced scorecard in view of its employees. As the researcher adopted the descriptive survey approach, and the questionnaire as the research instrument, which included (30) statements that were applied to a sample of (247) employees comprised of faculty members, and administrative staff at the university. The study has reached a set of results, the most important of which include: The research sample members agreed on the evaluation degree of the Private Prince Sultan University’s performance in light of the balanced scorecard with an arithmetical average of (3.61 of 5), namely, with a high agreement degree. With respect to dimensions, the beneficiaries (students) dimension came at the first rank with an average of (4.04 of 5), then, the learning and growth dimension with an average of (3.55 of 5), followed by the financial dimension with an average of (3.43 of 5), and finally the internal operations dimension with an average of (3.41 of 5) with a high degree agreement. In light of the study findings, the researcher recommended the empowerment of administrative staff, the development of their professional performance level, streamlining procedures and circulation of the organizational guides that control work, as well as establishing investment partnerships to develop its financial resources. In addition, the researcher also provides some proposals for prospective studies, namely, to conduct a study that addresses the evaluation of private universities’ performance in light of the balanced scorecard by applying this to other universities in other regions. As well as a study that investigates the challenges that encounter the performance of private universities in light of the balanced scorecard application.